Bacteriome and mycobiome profiling of liquid feed for finisher pigs on commercial pig farms - J. T. Cullen; P. G. Lawlor; P. Cormican; F. Crispie; H. Slattery; G. E. Gardiner (Scientific Reports)
Abstract The aim was to assess the quality of liquid feed for grow-finisher pigs across commercial pig farms by profiling the bacteriome and mycobiome of samples and determining biogenic amine concentrations. Amplicon sequencing of liquid feed samples revealed that bacterial and fungal community structures were influenced by the farm of origin and sampling location (mixing tank/trough) on a given farm. Decreases in alpha-diversity of liquid feed between the mixing tank and the troughs corresponded with increased relative abundances of bacteria, particularly Lactobacillus, Weissella and Leuconostoc, as well as yeasts, including Kazachstania and Dipodascus, indicative of spontaneous fermentation. The concentration of biogenic amines, resulting from amino acid loss from the feed, which likely plays a role in poorer feed efficiency, also increased between the mixing tank and the troughs. The highest biogenic amine concentrations in the feed were found on the farm that had the highest lactic acid bacteria (LAB) and yeast counts. Both Lactobacillus and Kazachstania were correlated with biogenic amine concentrations in liquid feed, highlighting the unexplored role that LAB and yeast may play in amino acid decarboxylation and biogenic amine formation in liquid feed. Factors including the use of liquid co-products in diets also impacted the liquid feed microbiome.